Study on Optimum Power Take-Off Torque of an Asymmetric Wave Energy Converter in Western Sea of Jeju Island - Haeng Sik Ko; Sangho Kim; Yoon Hyeok Bae (Energies, 2021)
This study primarily investigates an optimum energy conversion efficiency of asymmetric wave energy converter (WEC). A power take-off (PTO) system that provides a constant load torque opposite to pitch motion was implemented. Incident wave conditions were selected based on the measured data in the western sea of Jeju Island, South Korea. An optimum torque was calculated by comparing the time-averaged extracted power with various PTO load torque. InterDyMFoam solver based on Reynolds-averaged Navier-Stokes (RANS) equations were used in an OpenFOAM v4.0 framework—an open-source computational fluid dynamics model—against the experimental results derived from the wave flume. The upward pitch excursion was induced by wave force due to the asymmetric WEC characteristics; however, the downward pitch excursion depends on its weight. Numerically, the PTO torque was only loaded in uni-direction against the upward pitch motion. Moreover, the optimum PTO torque was estimated by comparing the time-averaged extracted power. Finally, the optimum PTO torque was evaluated by an irregular wave as a function of significant wave height. The optimum PTO provides design information about the asymmetric wave energy converter to improve energy conversion efficiency.